Why APIs? Anticipated value, barriers, and opportunities for standards-based application programming interfaces in healthcare: perspectives of US thought leaders - Gordon, William J; Rudin, Robert S (JAMIA open, 2022)
Objective Improving health data interoperability through application programming interfaces (APIs) is a focus of US policy initiatives and could have tremendous impact on many aspects of care delivery, such as innovation, operational efficiency, and patient-centered care. To better understand the landscape of API use cases, we interviewed US thought leaders involved in developing and implementing standard-based APIs. Materials and Methods We conducted semi-structured virtual interviews with US subject matter experts (SMEs) on APIs. SMEs were asked to describe API use cases along with value and barriers for each use case. Written summaries were checked by the SME and analyzed by the study team to identify findings and themes. Results We interviewed 12 SMEs representing diverse sectors of the US healthcare system, including academia, industry, public health agencies, electronic health record vendors, government, and standards organizations. Use cases for standards-based APIs fell into six categories: patient-facing, clinician-facing, population health and value-based care, public health, administrative, and social services. The value across use cases was viewed as unrealized to date, and barriers to the use of APIs varied by use case. Conclusions SMEs identified a diverse set of API use cases where standard-based APIs had the potential to generate value. As policy efforts seek to increase API adoption, our work provides an early look at the landscape of API use cases, value propositions, and barriers. Additional effort is needed to better understand the barriers and how to overcome them to create value, such as through demonstration projects and rigorous evaluations for specific use cases. Lay Summary Application programming interfaces (“APIs”) are a technical way of getting data out of a computer system. Recently, the United States passed legislation (the 21st Century Cures Act) requiring the use of APIs for electronic health record systems, which are where most healthcare providers document clinical encounters with patients and where other clinical data is held. In this article, we asked national experts in health information technology to describe some of the ways in which APIs could be used, how they are valuable, and what some barriers may be to broader use. We found 6 main categories, or “use cases,” for APIs in healthcare—patients, providers, administrative, public health, social services, and population-health. We also describe why these use cases are important, as well as barriers within each use case. As more and more health data are made available via APIs, these use cases will drive the success of these technological innovations.